CARDIOVASCULAR DISEASE RISK FACTORS IN OBESE ADULTS: AN INTEGRATIVE REVIEW (CIPEEX, 2022)
THE PRESENT STUDY AIMS TO CORRELATE RISK FACTORS FOR CARDIOVASCULAR DISEASE IN OBESE ADULTS. THE METHODOLOGY OF THIS MINI INTEGRATIVE REVIEW WAS CARRIED OUT USING THE PUBMED AND SCIELO ELECTRONIC DATABASES, ADOPTING THE DESCRIPTORS €ŒRISK FACTORS€, €ŒCARDIOVASCULAR DISEASES€, €ŒADULT€ AND €ŒOBESITY€. THE 5 STUDIES SELECTED AMONG THE 11 FOUND WERE EVALUATED AND THEIR SELECTION WAS BASED ON THEIR ABILITY TO RELATE TO THE OBJECTIVE OF THE REVIEW. AS A RESULT, IT CAN BE HIGHLIGHTED THAT THE ARTICLES ANALYZED MAKE A COMPILATION OF THE VARIOUS RISK FACTORS THAT CAN BE ADDRESSED IN THE SUBJECT OF CARDIOVASCULAR DISEASES AND PRESENT POINTS THAT ARE RELATED IN A WAY THAT COMPLEMENT EACH OTHER AND INCREASE THE STRENGTH OF THE STUDIES. THE GREATEST DIVERGENCE WAS PRESENTED IN THE ARTICLE BY SAADATI ET AL. (2021), WHO SHOWED THAT THE RISK FACTOR FOR CENTRAL OBESITY TENDS NOT TO BE AS INFLUENTIAL AS OTHER RISK FACTORS (HIGH SYSTOLIC PRESSURE AND INCREASED CAROTID INTIMA-MEDIA THICKNESS). THROUGH THE ANALYSIS OF THE DATA THAT WERE COLLECTED, IT CAN BE CONCLUDED THAT THE RISK FACTORS FOR CARDIOVASCULAR DISEASES IN OBESE ADULTS MOST POINTED OUT WERE THE HIGH BODY MASS INDEX THAT WAS ASSOCIATED WITH TRIGLYCERIDES, WITH ABDOMINAL CIRCUMFERENCE AND AGE. HIGH SYSTOLIC PRESSURE, HIGH LEVELS OF CRP (C-REACTIVE PROTEIN), PREVIOUS HISTORY OF MYOCARDIAL INFARCTION, HIGHER PREVALENCE OF HYPERTENSION, DIABETES, OBESITY AND SEDENTARY LIFESTYLE WERE ALSO IDENTIFIED AS VERY RELEVANT FACTORS IN CARDIOVASCULAR DISEASES.
Keywords: fatores de risco; doenças cardiovasculares; obesidade; adulto